Optimization of Tensile Strength in Resistance Spot Welding of Galvanized Steel Sheets Using 3k Factorial Design - Seksiri, Supakit; Lawong, Amin; Juntaree, Vichayut; Thanphonsri, Uthai; Sudsuansee, Thaithat; To-oon, Piyanat (Journal of Engineering and Industrial Technology, Kalasin University, 2024)
This research aims to study the optimal factors affecting the tensile strength of resistance spot welding on galvanized steel sheets. A 3K factorial design experiment was employed to analyze the influence of welding current and spot-welding distance. Two experiment setups were conducted: in Experiment model 1, the factors were welding current and distance along the Dy axis, while in Experiment model 2, the factors were welding current and distance along the Dx axis. The results indicate that both welding current, and distance significantly affect the tensile strength with normality testing and analysis of variance (ANOVA), using the statistical software Minitab (Version 18), and the optimal conditions for average maximum tensile strength were identified. For Experiment model 1, the optimal welding current was 600 amp with a distance of 5 mm, resulting in a tensile strength of 72.6852 kN/mm², and for Experiment model 2, the optimal welding current was 1800 amp with a distance of 15 mm, resulting in a tensile strength of 44.7037 kN/mm². This method can be used as a guideline for finding appropriate factors in cases where there is only one response value. and helps reduce trial and error from adjusting the settings of factors.